Government ownership and the association between corporate governance and CSR in the UAE - Farouq, Ayda; Sheikh Obid, Siti Normala; Annuar, Hairul Azlan (GRDS Publishing, 2015)
Why firms tend to participate in social activities or act responsibly is one of the main concerns in the current literature. Based on the stakeholder theory and stewardship theory this study assumed that the government ownership play the stewardship role in the firm. Particularly, the main objective of this study is to examine if the government ownership affect the firms services toward the community in UAE through imposing the implementation of the corporate governance mechanisms. Government ownership is assumed to affect the CSR either directly or indirectly by measuring the moderator effect of the government ownership on the association between the corporate governance and the CSR. Employing a sample of listed firms in United Arab Emirates (UAE) for the period from 2010 to 2013, it is found that the existence of the government ownership has a moderator effect on the association between the corporate governance mechanisms and the CSR. More specifically the research finds that the AC characteristics become more effective in improving the firms CSR when there are shares owned by the government. Moreover, the CSR of the firms with government ownership is found to outperform the CSR for firms without government ownership. This study comes to assure the vital role of the government in driving the country’s economy to growth.